Peran Industri Lembaga Keuangan Mikro Syariah Dalam Mengatasi Masalah Kesenjangan Dan Distribusi Pendapatan Di Kota Medan - K Kamilah; Annio Indah Lestari Nst (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
Medan City has just been chosen as the winner for the category of the Best City of Indonesia in 2017 and the Best City of the Sumatra Region. This shows the city's great potential in an effort to attract investors from various industries and business people as well as to advance the regional economy. However, the poverty rate in Medan among other cities in North Sumatra has increased continuously. As a result, the economic condition of the community in general has not reached the same level of income equity and deficiencies are still found, including the gap between regions in achieving economic levels. The abundance of research and scientific studies carried out in depth on the system originating from Islamic teachings, which proved to remain strong in the face of the crisis that came crashing, starting in 1998 and 2008 to the present. The purpose of this study is to look deeply into the role of the industry of Islamic microfinance institutions in overcoming the problem of social inequality and income distribution in Medan. This research method uses a qualitative descriptive method by means of case studies. The object of the research conducted in this study is the Role of the Industry of Sharia Microfinance Institutions in Medan City, while the subjects of this study are Practitioners, Employees of Islamic Microfinance Institutions (LKMS) and Customers of Islamic Microfinance Institutions (LKMS).The results of this study found that LKMS Madani Emas Syari’ah  has shown a fairly good role in its efforts to overcome the problem of social inequality, this was shown in an effort to help the capital of small and medium enterprises in Medan so that the business can continue despite limited funds, capital and resources. Even so, the role that is owned is not significant because in terms of the age of the newly established and only one LKMS that stands under the supervision of OJK in Medan City.